Avaliação técnico-econômica do processo de cogeração em uma indústria sucroalcooleira - Perea, Luiz Antonio [UNESP] (2005)
The study shows a revision of the situation of the Brazilian electric system, basically from the water that demanded the search of alternative sources of generation of electric energy, besides of the rationing event in 2001. One of the sources of energy is the biomass and especially the residues from the ground of the sugar cane. The Alcohol Sugar Cane Industry make use of bagasse from the sugar-cane as a source of energy, through the cogeneration process, consuming the electric energy or the heat energy, generated in its productive process, without excess to sale. With investments in boilers of high-pressure and generating turbo with a bigger capacity, this industry, making use of the same amount of bagasse and also the process of cogeneration, can come to generate excess of electric energy that would be commercialized as an alternative source of energy. This study analyzes the investments and technical feasible of a sugar mill, on the purpose of generate and sales the excess of electric energy. It was adopted the Program for growing of alternatives energy sources - PROINFA, as scene of price for selling energy in order to verify the results. It was considered the enterprise by finance from BNDES, denominate Program of financial support to investments in alternatives electrical power sources concern to PROINFA. The datos showing the technical viability of the enterprise. But the price of PROINFA for the biomass source of energy (sugar cane bagasse), the Net Present Value was negative and the Internal Rate of Return was lover that the Interest Rate, necessary for the economical viability of the enterprise, considering the normal time of sugar cane season.